O której godzinie „święty ogień” zstępuje do Grobu Pańskiego? Kilka uwag na marginesie polskich przekładów najstarszego ruskiego itinerarium - Hodana, Tomasz (Przegląd Rusycystyczny, 2013)
Tomasz Hodana Uniwersytet Jagielloński, Kraków, Poland hodana@interia.pl В КОТОРОМ ЧАСУ "БЛАГОДАТНЫЙ ОГОНЬ" НИСХОДИТ В ГРОБ ГОСПОДЕНЬ? НЕСКОЛЬКО ЗАМЕТОК НА ПОЛЯХ ПОЛЬСКИЬ ПЕРЕВОДОВ ДРЕВНЕЙШЕГО РУССКОГО ХОЖДЕНИЯ Резюме Статья является комментарием к двум польским переводам Хожения игумена Даниила, классического произведения древнерусской письменности, созданного в начале XII в. Автор статьи сосредотачивает внимание на ошибках, появившихся в польскоязычных вариантах описания великосубботней церемонии Святого Света в иерусалимском храме воскресения Христова. непоследовательность и ошибки, наблюдаемые в обоих польских переводах данного фрагмента Хожения, связаны с неправильным пониманием выражений «часы ночи» и «часы дня». Эти определения встречаются также в ряде книг Священного Писания и отражают характерное для Палестины понимание суток и очередных времен ночи и дня. AT WHAT TIME “THE HOLY FIRE” DESCENDS TO THE HOLY SEPULCHRE? SOME REMARKS ON THE MARGIN OF POLISH TRANSLATIONS OF THE OLDEST TRAVELOGUE OF KIEVAN RUS’ Summary The article comments on the two Polish translations of The Pilgrimage of the Abbot Daniel, a classic work of travel writing of Kievan Rus’, which was written in the early 12th century. The author focuses on describing translation errors which occur while detailing the descent of the “Holy Fire” ceremony, which took place on Great Saturday in the Church of the Holy Sepulchre in Jerusalem. The errors and inconsistencies found in both Polish translations in this particular passage stem from a misunderstanding of the original terms “hours of the night” and “hours of the day”. These terms, used also by the authors of the books of the Bible, reflect the characteristic Palestinian way of understanding day as well as the way of identifying parts of the night and day.